Modificação da molhabilidade da celulose por processos subsequentes de ablação e deposição a plasma - Camargo, Janine Sanches Gonzaga de (2017)
Cellulose is a biopolymer available in abundance in nature, which presents very interesting properties mainly for the textile, packaging and paper industry. However, due to its strongly hydrophilic character, resulting from the presence of a large number of free hydroxyl groups in its molecule, its use in certain areas becomes limited. In order to promote the modification of the wetting characteristic of the cellulose, and make it superhydrophobic, samples of this material were submitted to plasma processes performed in two steps: ablation and film deposition. Initially, the effect of variation of ablation time on the creation of adequate surface topography was studied. For this, the samples were exposed to the oxygen plasma at a pressure of 13 Pa and power of 150 W, varying the treatment time from 5 to 60 minutes. Then, the treated samples were submitted to the process called PECVD (Plasma Enhanced Chemical Vapor Deposition), in which a film was deposited on the surface from the precursor hexamethyldisiloxane (HMDSO) in the presence of argon, in a ratio of 70 e 30%, respectively. The deposition time was set to 30 minutes and the power applied was 150 W. In a second investigation, the effect of the thickness of the deposited film was studied. In this case, the cellulose samples were previously exposed to the oxygen ablation plasma for 60 minutes and then led to the PECVD process, with the deposition time varying from 5 to 30 minutes. In a third investigation, the duration of the ablation and deposition steps was reduced to 30 and 1 minute, respectively, in order to optimize the methodology. The samples were characterized by Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FTIR), profilometry, static contact angle measurements and hysteresis and sliding angle measurements. The results demonstrated that longer exposure times for the ablation step provide a significant modification in the material, through the creation of nanoscale structures on the surface of the fibers. The deposition step promoted the formation of films with organosilicon character on the cellulose surface, with thicknesses varying between 144 and 910 nm. The combination of the topography created after 30 minutes of ablation with the thin film resulting from the deposition step for 1 minute provided a surface with low receptivity for both polar (? = 150°) and nonpolar (? ~ 120°) liquids, whose wettability property remained stable with treatment aging time. The low values obtained for hysteresis (9°) and sliding angle (7°) confirm the creation of a superhydrophobic roll-off surface.